Two baby girls with PHACE syndrome treated with propranolol. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 2-month-old baby presented with extensive hemangioma of the face involving the forehead, mainly on the right, nose and lip, especially lower (Fig. 1, 2). The baby also had Dandy-Walker syndrome (Fig. 3) and had undergone two neurosurgical operations for concomitant hydrocephalus. She had no anomalies of the great vessels of the neck and chest, but had multiple septal defects with small shunt left>right at high speed. The clinical diagnosis was PHACE syndrome. Under cardiac monitoring she started propranolol 2 mg/kg per day, which led to a rapid improvement (Fig. 4) without side effects. The therapy was withdrawn at the age of 1 year without a rebound growth of hemangioma. Case 2. A 75-day-old baby presented with congenital hypothyroidism treated with thyroxine and large hemangioma of the left hemiface (Fig. 5, 6). MRI ruled out changes in the brain and blood vessels of the neck and chest. The eye examination showed on the left a "morning glory" papilla (Fig. 7 and inset) leading to the diagnosis of PHACE syndrome. Under heart monitoring she started propranolol 2 mg/kg per day, which led to a rapid improvement (Fig. 8) with no side effects. The clinical improvement of hemangioma was associated with worsening of hypothyroidism leading to increase twice the dose of thyroxine. The therapy with propranolol was suspended at 1 year without rebound growth of hemangioma.